Evaluation of a transdiagnostic mental health intervention in German primary care: study protocol for a parallel-group, two-arm, cluster randomised controlled pilot study - Christopher Ebert; Marie Vogel; Jochen Gensichen; Hanna Reif; Lena Grögor; Lukas Junker; Thomas Ehring; Alkomiet Hasan; Stefan Leucht; Kirsten Lochbühler; for the POKAL-Group (Pilot and Feasibility Studies)
Abstract Background General practitioners play an important role in the first-line care of individuals with mental health conditions. However, factors such as time constraints, limited experience in managing mental health conditions and high rates of comorbidity may hinder adequate treatment. To improve psychological care, adopting a transdiagnostic approach shows potential. Research on transdiagnostic interventions delivered by general practitioners is scarce. Thus, a transdiagnostic intervention adapted from the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders was developed specifically for primary care. In a parallel-group, two-arm, cluster randomised controlled pilot study, the transdiagnostic intervention will be evaluated for feasibility, acceptability and potential effectiveness in German primary care. Methods A total of 100 adult patients with a mental health condition will be recruited by general practitioners. In the intervention group, general practitioners will administer the transdiagnostic intervention, introducing patients to psychological concepts based on transdiagnostic factors (i.e., understanding emotions, cognitive flexibility, countering emotion-based avoidance). In the control group, general practitioners will provide improved treatment as usual oriented on official German treatment guidelines for depression, anxiety and somatoform disorders. In both study groups, treatment will be carried out in four 20-min sessions over 12-weeks. Self-report questionnaires will be completed before treatment initiation (only patients) and after treatment completion (patients and general practitioners) to assess feasibility and acceptability (i.e., treatment recruitment, delivery, response, effectiveness, unintended consequences and maintenance) as well as potential effectiveness (i.e., change in transdiagnostic factors). Discussion The pilot study will address the research gap concerning general practitioner-led psychological interventions in primary care and will give insights into whether the adoption of a transdiagnostic approach is of benefit to general practitioners and patients. Findings may inform the design of a main trial by identifying barriers to the transdiagnostic intervention’s feasibility and acceptability, whilst advancing treatment delivery protocols to support effectiveness. Trial registration The protocol for this study has been registered with the German Clinical Trials Register: DRKS00033386, Date of registration: 18th of March 2024, https://drks.de/search/en/trial/DRKS00033386 .